1, 4‐Bis(2, 3‐dicarboxyl‐phenoxy)benzene dianhydride‐based phenylethynyl terminated thermoset oligoimides for resin transfer molding applications. Issue 38 (16th May 2019) - Wang, Wei; Chen, Guofei; Fang, Xingzhong
ABSTRACT: A series of thermoset oligoimides have been prepared by the thermal polycondensation of 1, 4‐bis(2, 3‐dicarboxyl‐phenoxy)benzene dianhydride with three different aromatic diamines in the presence of 4‐phenylethynylphthalic anhydride as an end capping reagent. The aromatic diamines included 4, 4′‐oxydianiline, 2, 2′‐bis(trifluoromethyl)benzidine (TFDB) and 2‐phenyl‐4, 4′‐diaminodiphenyl ether ( p ‐ODA). Effects of the chemical structures and molecular weights of the oligoimides on their aggregated structures, melt processability as well as the thermal and mechanical properties of the cured films were then systematically investigated. X‐ray diffraction results indicated that ODA series oligoimides and TFDB series oligoimides showed crystallinity; however, the asymmetrical p ‐ODA enables the p ‐ODA series oligoimides to exhibit amorphous forms. So the p ‐ODA based oligoimides with molecular weight of 750 g mol −1 showed much lower melt viscosity at a low temperature and the melt viscosity could maintain below 1 Pa s −1 after isothermal aging for 2 h at any temperature in the range of 220–280 °C by rheological measurements. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47967. Abstract : A big progress has been made in the melt processability of the oligoimides for RTM process.